Desenvolvimento experimental de um protótipo do motor stirling modelo alfa - Araújo, Liliane Ferreira (Universidade Federal Rural do Semi-Árido, 2017)
This work deals with the experimental development of a didactic prototype of the Stirling engine with Alpha configuration, whose dimensional parameters were established based on already developed prototypes. The experimentation aims at the collection of pertinent information, such as constructive characteristics and parameters essential to the performance of the engine. The main components of the prototype consist of 10- and 20-ml glass syringes that act as cylinders and pistons required to generate the reciprocating motion that is turned into rotary motion through a crank-crank mechanism. Uses air as working fluid. Much of the materials used in the manufacture of the same consist of reused components that supply the need for the operation. Through the construction and analysis of the prototype it was possible to perform a dynamic evaluation of the behavior of the engine in response to different masses of the flywheel, the increase of the compression ratio and the different fuels, as well as to list the possible problems related. The main conclusions were the need for a high calorific fuel for a high volume of working fluid, as well as larger flywheel mass for high torque and power output. In addition, care with the dimensions of the components is essential to the operation of the prototype.
Monografia
Keywords: Motor Stirling; Alfa; Avaliação dinâmica; Massa do volante; Taxa de compressão; Combustível; Engine Stirling; Alfa; Dynamic evaluation; Steering wheel mass; Compression ratio; Fuel; ENGENHARIAS::ENGENHARIA MECANICA